Prevalence of MPL (W515K/L) Mutations in Patients with Negative-JAK2 (V617F) Myeloproliferative Neoplasm in North-East of Iran - Seyyede Fatemeh Shams; Hossein Ayatollahi; Mohammad hadi Sadeghian; Monavar Afzal Aghaee; Sepideh Shakeri; Ehsan Yazdandoust; Maryam Sheikhi; Nafiseh Amini; Samane Bakhshi; Afsane Bahrami (Iranian Society of Pathology, 2018)
Background and Objective: Janus kinase 2 (JAK2) and Myeloproliferative Leukemia (MPL) mutations are confirmatory indicators for Myeloproliferative Neoplasm (MPN). The current study was performed to determine the frequency of MPL mutation in MPN patients without JAK2 mutation, in order to assign MPL mutation frequency in North-East of Iran.Methods: Total of 105 negative JAK2 cases including 5 Myeloproliferative Disorders (MPD), 15 Polycytemia Vera (PV) and 15 Essential Thrombocytosis (ET) who referred to Qaem Medical Center were assigned to this study. ARMS-PCR was carried out for measuring MPL mutations. Results: A significant difference was observed between MPL mutant and non-mutant groups from overview of MPL mutation (P=0.00001). From the total studied population, 14.28% were ET cases and 4.71% of them had splenomegaly. About 66.66% had thrombocytosis and 33.33% of all the individuals had leukocytosis according to WHO criteria, and 4.76% of non-MPL mutant individuals had splenomegaly (P=1). This mutation was reported in 4-6% of ET and PMF individuals. In this research, 4.76 % of studied individuals had MPL (W515L/K) mutation, which were diagnosed with ET.Conclusion: Generally, the presence of JAK2 and MPL mutations are the most important criteria for MPN diagnosis. The obtained frequency of MPL mutation was similar to previous studies. Despite the high frequency of JAK2 and Philadelphia abnormality, MPL mutation was rare in myeloprolifrative disorders. Further studies are suggested to investigate its prognostic effects for these diseases.